2002
DOI: 10.1002/1521-3900(200209)187:1<77::aid-masy77>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The wet adhesion of water borne acrylic dispersions is a crucial factor on the performance of outdoor coatings on wood. Pine sapwood was treated with several methods for surface activation to increase the wet adhesion of water borne acrylic dispersions. The wet adhesion was measured by pull‐off tests as well as with a modified cross‐cut test. Atmospheric plasma, corona treatment and fluorination increased the wet adhesion of the coating which is attributed to the increasing polar portion of the surface free en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Plasma pre-treatments have also been tested for their ability to improve the adhesion and performance of glues and coatings on wood, and wood composites [6][7][8][9][10]. For example, several studies have examined whether plasma treatments can improve the adhesion of coatings to solid wood [11][12][13][14][15][16][17][18][19]. The results have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma pre-treatments have also been tested for their ability to improve the adhesion and performance of glues and coatings on wood, and wood composites [6][7][8][9][10]. For example, several studies have examined whether plasma treatments can improve the adhesion of coatings to solid wood [11][12][13][14][15][16][17][18][19]. The results have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have obtained mixed results. For example, both Back and Danielsson [14], and Lukowski and Hora [15] showed that plasma pre-treatments increased the adhesion of aqueous acrylate dispersions to wood, but had no such effect on the adhesion of solvent-borne coatings. Increases in the adhesion of coatings to plasma-modified wood also vary with wood species, as well as coating type [16].…”
Section: Introductionmentioning
confidence: 99%